PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS MODEL DISCOVERY LEARNING PADA MATERI LISTRIK - imam Yaskur; Indica Yona Okyranida; Asep Setiadi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2023)
This study aims to determine the feasibility of physics learning modules based on Discovery Learning on Electricity and to determine student responses to the modules that have been developed. The research method used is the R&D (Research and Development) method. The results of this study obtained an average final validation test score of 88% in the "Very feasible" category. After conducting a small-scale test on 10 students and getting an average student response score of 3.5 or 87.50% in the "good" category